Synthesis and structure of tris(2-methyl-1H-imidazol-3-ium) 5-carboxybenzene-1,3-dicarboxylate 3,5-dicarboxybenzoate - Lina Maria Asprilla-Herrera; Simone Techert; Jose de Jesus Velazquez-Garcia (Acta Crystallographica Section E: Crystallographic Communications)
The structure of the title salt, 3C4H7N2+·C9H5O6−·C9H4O62−, 1, consists of three 2-methyl-imidazolium cations and both a single and a doubly deprotonated form of trimesic acid as anions. A detailed analysis of the bond lengths and angles reveals both differences and similarities between compound 1 and the previously reported 2-methyl-1H-imidazol-3-ium 3,5-dicarboxybenzoate structure [Baletska et al. (2023). Acta Cryst. E79, 1088–109], as well as the neutral counterpart of the ions. Examination of the crystal packing shows the formation of infinite chains by the anions, which, along with the cations, form zigzag planes parallel to the ab plane. The packing interactions are primarily driven by π–π interactions and hydrogen bonding between anions.